PENGARUH SELF-EFFICACY DAN BUDAYA ORGANISASI TERHADAP PROFESIONALISME ANGGOTA KEPOLISIAN DAERAH (POLDA) DAERAH ISTIMEWA YOGYAKARTA - Musa Masing (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine: 1) the influence of self-efficacy on the professionalism of the Special Region of Yogyakarta Regional Police members, 2) the influence of organizational culture on the professionalism of the Special Region of Yogyakarta Regional Police members, 3) the influence of self-efficacy and organizational culture on the professionalism of the Special Region of Yogyakarta Regional Police members. The sample are 397 people. The data collection used a self-efficacy scale, organizational culture scale, and professionalism scale. Data analysis used multiple linear regression. The results are: 1) there is a positive effect of self-efficacy on professionalism in Regional Police members with a correlation value of 0.814 (p <0.05); 2) there is a positive influence of organizational culture on professionalism in Regional Police members with a correlation value of 0.742 (p <0.05); 3) there is an influence of self-efficacy and organizational culture on the professionalism of members of Regional Police, the F value is 421,904 (p < 0.05) with an R-value of 0.826. The effective contribution of self-efficacy and organizational culture to the professionalism of the Special Region of Yogyakarta Regional Police members by 68% while the remaining 34% is the influence of other variables not examined in this study